2008
DOI: 10.1111/j.1600-0560.2007.00841.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of survivin and NF‐κB in psoriasis, an immunohistochemical study

Abstract: Background: Suppression of apoptosis is generally one of the accepted pathogenetic mechanisms for psoriasis and any epidermal hyperproliferative states. Survivin is a member of the inhibitor of apoptosis protein family mediating its apoptosis suppressive function by the inhibition of caspase pathway. Nuclear factor kappa B (NF-kB) is a transcription factor that regulates hundreds of genes including many critically involved in apoptosis. The aim of this study was to explore the role could be played by survivin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 23 publications
2
45
0
1
Order By: Relevance
“…Total expression of the proteins forming NF-κB, the heterodimer p50 and p65, may not be increased in psoriatic lesions [56], but the active phosphorylated form or nuclear expression of NF-κB is detected in 66% of psoriatic lesions and overexpressed in psoriasis compared with normal skin [57]. In addition, NF-κB function appears deregulated, in the sense that NF-κB DNA binding to the p53 k Bsite is decreased, whereas NF-κB binding to the pro-inflammatory interleukin-8 (IL-8) κB site is increased in lesional psoriatic skin compared with non-lesional psoriatic skin [58].…”
Section: Human Use Of Chondroitin Sulphatementioning
confidence: 99%
“…Total expression of the proteins forming NF-κB, the heterodimer p50 and p65, may not be increased in psoriatic lesions [56], but the active phosphorylated form or nuclear expression of NF-κB is detected in 66% of psoriatic lesions and overexpressed in psoriasis compared with normal skin [57]. In addition, NF-κB function appears deregulated, in the sense that NF-κB DNA binding to the p53 k Bsite is decreased, whereas NF-κB binding to the pro-inflammatory interleukin-8 (IL-8) κB site is increased in lesional psoriatic skin compared with non-lesional psoriatic skin [58].…”
Section: Human Use Of Chondroitin Sulphatementioning
confidence: 99%
“…The pathophysiology of psoriasis is complex and has not been completely elucidated. Current studies show that abnormal proliferation and differentiation of keratinocytes as well as prominent immune cell infiltration contribute to psoriasis development (Abdou & Hanout, 2008). Consistently, inhibition of the excessive proliferation of keratinocytes and proinflammatory responses has proved to be efficient methods for psoriasis treatment.…”
Section: Introductionmentioning
confidence: 98%
“…Compared to normal skin, NF-kB was significantly overexpressed in psoriatic skin [73], and compounds that inhibit NF-kB translocation result in improvement of disease severity [74,75]. Investigators have also observed that, in the epidermis of psoriatic skin, there is an upregulation of NF-kB activity, and anti-TNF-a therapy leads to down-regulation of NF-kB [76].…”
Section: Ros-influenced Pathways In Psoriasismentioning
confidence: 95%